Preparation method of moisture generator based on waste incineration fly ash and waste salt

By washing and sonicating the fly ash aqueous solution, combining carbon materials and surfactants, a high-performance moisture generator is prepared, which solves the problems of complex and high cost of material treatment in the prior art, and realizes the effective waste incineration of fly ash Utilize, adapt to wide climate humidity and reduce equipment costs.

CN119210215APending Publication Date: 2024-12-27ZHEJIANG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411333469.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing moisture power generation technology has complex material processing technology, high cost, and lacks methods to prepare moisture generators using waste incineration fly ash, making it difficult to achieve sustainable and green energy development.

Method used

By washing the waste and incinerating the fly ash, obtaining a fly ash aqueous solution that removes heavy metals, mixes carbon materials and surfactants, and after ultrasonic treatment, coats it on the non-woven fabric to form a conductive carbon cloth, and adds the fly ash aqueous solution several times to build a carbon cloth. To achieve the preparation of a moisture generator.

Benefits of technology

It has realized the use of waste incineration fly ash to prepare high-performance moisture generators, which has reduced material costs, adapted to a wide range of climate and humidity, ensured the stability and performance of equipment, and promoted the development of green energy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119210215A_ABST
    Figure CN119210215A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a moisture generator based on waste incineration fly ash waste salt, which comprises the following steps: washing waste incineration fly ash to obtain a fly ash aqueous solution, adjusting the pH value of the fly ash aqueous solution to 8.5-9.5, and carrying out solid-liquid separation to obtain a fly ash aqueous solution without heavy metal ions; the preparation method comprises the following steps: mixing a carbon material and a surfactant to obtain mixed powder, adding the mixed powder into deionized water, performing ultrasonic treatment to obtain a conductive dispersion liquid, and coating and drying the conductive dispersion liquid on the surface of a non-woven fabric for multiple times until a preset resistance value is reached to obtain carbon cloth; dropwise adding a fly ash aqueous solution without heavy metal ions into one end of the carbon cloth until the carbon cloth is completely absorbed, drying, and dropwise adding and drying for many times to obtain waste salt moisture driven carbon cloth; and connecting the waste salt moisture driving carbon cloth with a wire to obtain the moisture generator. According to the preparation method, the moisture generator with good performance can be manufactured by utilizing the waste incineration fly ash, and the technology is consistent with the green energy development direction and the energy development concept of waste recycling.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the fields of wet gas power generation and solid waste resource utilization, and specifically relates to a preparation method of a wet gas generator based on fly ash and waste salt from garbage incineration. Background Art

[0002] Due to the ongoing burden of energy crisis and global warming, finding sustainable and green energy is an urgent challenge for human society. Fortunately, the natural hydrological cycle is a huge energy carrier on Earth, storing and transferring huge amounts of clean energy through evaporation, evapotranspiration, convection, precipitation, snowmelt and runoff. It is estimated that water absorbs and releases up to 60 PW (10 15 W) of energy, which is three orders of magnitude higher than the global annual energy consumption. However, hydroelectricity currently utilizes only very limited kinetic and gravitational energy technologies (about 10 12 W).

[0003] With the rapid development of nanotechnology and nanomaterials, extracting energy directly from the hydrological cycle is becoming a reality. Hygroscopic power generation technology based on directional ion migration or selective ion transport can convert chemical potential energy during moisture absorption or latent heat during natural evaporation into electricity, showing the potential to alleviate energy shortage problems. Compared with traditional energy storage devices that usually require complex structures and the resulting high costs, hygroscopic power generation technology is considered to be the next generation of energy supply technology because of its high environmental adaptability and the lack of additional stimulation.

[0004] Due to the lack of sustainable and sufficient free water capture mechanisms and structures, current hygroscopic power generation devices suffer from discontinuous power generation and low energy density. Achieving continuous, easily scalable and high-performance hygroscopic power generation is a huge challenge and has so far been difficult to meet the needs of practical levels.

[0005] The invention patent application with the publication number CN117578912A discloses a method for preparing a wet gas generator and a wet gas generator, the method comprising the following steps: acidifying a polyethylene terephthalate (PET) cold mounting film with dilute hydrochloric acid; attaching a layer of carbon material electrode to the PET cold mounting film to form a double-layer structure electrode, and encapsulating it with conductive glue to build a wet gas generator frame; then brushing an electrolyte solution on the wet gas generator frame and the carbon material electrode, the solute of the electrolyte solution is one of lithium chloride, magnesium sulfate, phosphorus pentoxide, aluminum oxide, copper sulfate, and calcium sulfate; encapsulating a wire on the carbon material electrode, and encapsulating the exposed electrode surface with conductive glue to make a wet gas generator. The method for preparing a wet gas generator and the wet gas generator of the present invention can achieve a higher open circuit voltage at the same temperature and relative humidity by adding an electrolyte solution to the wet gas generator.

[0006] The invention patent application with the publication number CN116247969A discloses a polymer wet gas generator based on porous support, a preparation method and an application, which belongs to the field of wet gas power generation technology. The polymer wet gas generator is assembled by a positive electrode, an active layer and a negative electrode in a sandwich structure; the active layer is composed of a porous polyurethane foam and a polystyrene sulfonic acid solution, and the composite material is used to provide movable ions and is responsible for the adsorption, diffusion and evaporation channels of water; the negative electrode is an active electrode aluminum mesh, and the positive electrode is a conductive glass. The wet gas generator can obtain energy from air moisture in an all-weather environment and convert it into clean energy. Its main principle is to use the hydrovoltaic effect. Water moves in a directional manner along the humidity gradient inside the composite material, and the separation and movement of charges are generated on the microscopic surface where the material contacts the water, so that it is manifested as an electrical output on both sides with a humidity difference. The porous characteristics ensure the moisture circulation path of the device and the performance stability of the device.

[0007] As can be seen from the above two patents, the existing manufacturing technology and the material handling process for manufacturing wet gas power generation devices are relatively complicated, involving plasma oxidation, chemical oxidation and electric field induction, etc.; the raw materials for preparation are also difficult to obtain, and are usually mainly graphene oxide, nanocarbon materials, porous polymers, and polymer membranes, which are costly and difficult to obtain.

[0008] However, there has been no report on making a wet gas generator from waste incineration fly ash, so there is an urgent need to provide a preparation method that can make a wet gas generator from waste incineration fly ash. Summary of the invention

[0009] The present invention provides a method for preparing a wet gas generator based on waste incineration fly ash and waste salt. The preparation method can utilize waste incineration fly ash to produce a wet gas generator with better performance, which is consistent with the development direction of green energy and the energy development concept of waste recycling.

[0010] A method for preparing a wet gas generator based on fly ash and waste salt from garbage incineration, comprising:

[0011] (1) washing waste incineration fly ash to obtain a fly ash aqueous solution, adjusting the pH value of the fly ash aqueous solution to 8.5-9.5, and obtaining a fly ash aqueous solution from which heavy metal ions are removed after solid-liquid separation;

[0012] The carbon material and the surfactant are mixed to obtain a mixed powder, the mixed powder is added to deionized water, and ultrasonic treatment is performed to obtain a conductive dispersion, and the conductive dispersion is coated and dried on the surface of the non-woven fabric for multiple times until a preset resistance value is reached to obtain a carbon cloth;

[0013] (2) adding a fly ash aqueous solution from which heavy metal ions have been removed to one end of the carbon cloth until the carbon cloth has completely absorbed the ions and then drying the solution, and repeating step (2) multiple times to obtain a waste salt moisture driven carbon cloth;

[0014] (3) Connect the waste salt moisture-driven carbon cloth to the wire to obtain a moisture generator.

[0015] Preferably, the stirring time of the water washing is 1 to 1.5 hours, the rotation speed is 800 to 1200 r / min, and the liquid-solid ratio of the aqueous solution to the waste incineration fly ash is (3 to 5): 1 (L / kg). By controlling the amount of the aqueous solution, the stirring time and the rotation speed, the chlorine salt water of the waste incineration fly ash is washed into the fly ash aqueous solution.

[0016] Preferably, the pH value of the fly ash aqueous solution is adjusted by hydrochloric acid with a concentration of 1 to 2 M, and the volume of the hydrochloric acid is 10% to 15% of the fly ash aqueous solution.

[0017] Preferably, the solid-liquid separation method is filter pressing or centrifugation.

[0018] Preferably, the salinity of the fly ash aqueous solution from which heavy metal ions are removed is 10 wt% to 20 wt%.

[0019] Preferably, before the fly ash aqueous solution from which heavy metal ions are removed is dripped onto one end of the carbon cloth, the mass concentrations of Na, K and Ca ions and the corresponding masses of chloride salts in the fly ash aqueous solution from which heavy metal ions are removed are measured, and based on pre-set chloride salt mass standards for Na, K and Ca ions, additional chloride salts that do not meet the standards are added.

[0020] Further preferably, the Ca ion concentration in the fly ash aqueous solution from which heavy metal ions are removed is between 60% and 70%.

[0021] Further preferably, the chloride salt includes NaCl, KCl or CaCl2, with a mass fraction of more than 99%.

[0022] The mass ratio of Na, K and Ca mixed chloride salts in the fly ash water for removing heavy metal ions provided by the present invention can be set by oneself or follow the existing ratio in the fly ash water washing liquid. Different mixed salt systems have different hygroscopic properties. Further preferably, taking into account the ratio of chloride salt components in the waste incineration fly ash water washing liquid used in this case and the hygroscopic performance requirements of the mixed chloride salts, the mass ratio of Na, K and Ca ion concentrations in the water washing liquid used in this case is 1:1:3.

[0023] Preferably, the mass ratio of the carbon material to the surfactant is 1:(2-3).

[0024] Preferably, the carbon material is conductive carbon black, and the surfactant is dodecyltrimethylammonium bromide.

[0025] Preferably, in the conductive dispersion, the content of the carbon material is 5-10 g / L, and the ultrasonic time is 1-2 h. The present invention controls the content of the carbon material and the ultrasonic time so that the carbon material can be evenly dispersed in the conductive dispersion, thereby allowing the carbon material to be more evenly loaded on the non-woven fabric and avoiding the formation of clusters due to excessive carbon material content that causes sinking to the bottom.

[0026] Further preferably, the power of the ultrasound is 800-1000W and the temperature is 60-70°C.

[0027] Preferably, the resistance value of the carbon cloth is 5-20 kΩ.

[0028] Preferably, the conductive dispersion is repeatedly coated on the surface of the non-woven fabric and dried 8-10 times.

[0029] Preferably, step (2) is repeated 4-6 times.

[0030] Preferably, the chloride content of the waste salt moisture-driven carbon cloth is (0.04-0.08) g / cm 2 By controlling the chloride salt content, the appropriate chloride salt loading can control the amount of moisture absorption while providing sufficient electrical signals, thereby improving the stability of the wet gas generator.

[0031] Preferably, step (3) comprises the following steps:

[0032] One side of the waste salt moisture-driven carbon cloth is connected to a wire, and the side not connected to the wire is insulated and packaged to obtain a moisture generator unit.

[0033] According to the design requirements, multiple units can be connected in series or in parallel to obtain a hygroscopic generator with better performance. It is fixed on an insulating and breathable base, placed in a special container with constant temperature and humidity, and connected to the external circuit test system with copper wires.

[0034] Description of the invention principle:

[0035] The present invention combines the waste salt recovery work of hazardous waste incineration fly ash, and utilizes the hygroscopic power generation technology based on directional ion migration or selective ion transport to convert the chemical potential energy during hygroscopic period into continuous electrical energy.

[0036] The technical principle is described as follows:

[0037] (1) Mechanism and composition of wet gas generator:

[0038] Generally, a wet gas generator can be divided into three parts, such as Figure 1Shown: a hygroscopic part with superhydrophilicity for ample water supply; a transport part with abundant nanochannels for directional water transport; and an evaporative part with weak water affinity for natural evaporation of water. The key factor to achieve hygroscopic power generation is to construct heterogeneous structures with different water affinities. When exposed to the environment, the hygroscopic part will spontaneously absorb water from the ambient air, forming a water content gradient in the hygroscopic generator device. Benefiting from the abundant nanochannels and nanopores in the transport part, the absorbed water will flow from the hygroscopic part to the evaporative part driven by the water content gradient. Under ambient conditions, the water stored in the evaporative part will evaporate spontaneously because the partial pressure of water in the air is always lower than the saturated vapor pressure. Finally, the vapor pressure difference between the hygroscopic part and the vicinity of the evaporative part drives the water molecules to complete convection, establishing a persistent artificial water cycle for continuous power generation.

[0039] (2) Auxiliary moisture absorption and potential amplification of hygroscopic salts:

[0040] Hygroscopic materials directly determine the hygroscopic capacity of hygroscopic generators and are considered to be one of the key factors affecting environmental adaptability and ensuring water supply. Hygroscopic materials require relative humidity (RH) to collect moisture from the air. The chloride salts contained in fly ash water wash are mainly sodium potassium calcium chloride salts, of which calcium chloride accounts for more than 60% by mass. Calcium chloride can absorb moisture in an environment with RH ≥ 30%, which can basically adapt to the climate humidity in most parts of my country and ensure normal operation.

[0041] In addition, some scientific studies have shown that metal cations in hygroscopic salts can generate additional charges to form EDLs, thereby increasing power generation. The size, charge, and solubility of these ions strongly affect their behavior during charge redistribution. Specifically, for chloride salts of alkali metals (monovalent) or chloride salts of alkaline earth (divalent) metals, higher voltages are usually generated in solutions with smaller cation radii. So we can use hygroscopic salts to amplify the performance of hygroscopic generator materials.

[0042] Based on the above principles, the present invention couples wet gas power generation technology with waste salt extraction to achieve functional utilization of soluble chloride salts contained in fly ash from hazardous waste incineration, prepare advanced energy material equipment, and realize the linkage combination of material circulation (waste utilization) and energy development (free natural water potential energy power generation). First, the heavy metal leaching in the fly ash washing process is reduced by adjusting the pH. When the pH is about 9, heavy metals such as Zn, Pb, Cu, and Ni in the fly ash are retained in the washed ash without migrating into the washing liquid, preventing interference with the subsequent chloride salt loading process. Conductive carbon black and surfactants are mixed with water and ultrasonically treated to make them evenly dispersed. Conductive carbon black is repeatedly loaded with hydrophilic non-woven fabrics to obtain a conductive water-transmitting wet gas generator skeleton, and then fly ash washing liquid is repeatedly added at one end until the mixed chloride salt is reasonably and stably loaded.

[0043] Compared with the prior art, the present invention has the following advantages:

[0044] The present invention controls the pH value of the fly ash aqueous solution so that heavy metals such as Zn, Pb, Cu, Ni and the like are retained in the fly ash solid and do not migrate into the water washing liquid, thereby preventing interference with the subsequent chloride salt loading process. The fly ash aqueous solution obtained by solid-liquid separation contains a large amount of chloride salts, which are mainly sodium potassium calcium chloride salts, of which the mass proportion of calcium chloride is more than 60%. The calcium chloride can absorb moisture in an environment of RH≥30%, and can basically adapt to the climate humidity in most areas of my country, thereby ensuring normal moisture absorption.

[0045] The present invention constructs a wet gas generator skeleton by coating and drying a conductive dispersion on a hydrophilic non-woven fabric, and then forms a salt gradient in the carbon cloth by soaking and drying the fly ash aqueous solution from which heavy metal ions have been removed multiple times at one end of the carbon cloth, thereby forming a humidity difference and then realizing an electric potential difference to achieve the function of wet gas power generation. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A flow chart of a method for preparing a wet gas generator based on waste incineration fly ash and waste salt provided in a specific embodiment of the present invention;

[0047] Figure 2 A schematic diagram of a moisture gradient structure of a wet gas generator based on utilization of fly ash and waste salt from waste incineration provided in Example 1;

[0048] Figure 3 A moisture gradient volt-ampere characteristic diagram of a wet gas generator based on the utilization of waste incineration fly ash and waste salt provided in Example 1, Figure 3 (a) is the current characteristic change diagram under different humidity gradients. Figure 3 (b) is the voltage characteristic change diagram under different humidity gradients;

[0049] Figure 4 A 24-hour long cycle power generation voltage diagram of a wet gas generator based on the utilization of fly ash and waste salt from garbage incineration provided in Example 1;

[0050] Figure 5 A series voltage increase diagram and a parallel current increase diagram of a wet gas generator based on the utilization of fly ash and waste salt from garbage incineration are provided as an extension of Example 1, wherein: Figure 5 (a) is the parallel current; Figure 5 (b) is the series voltage. DETAILED DESCRIPTION

[0051] The present invention is further described below by way of embodiments in conjunction with the accompanying drawings, but the present invention is not limited thereto.

[0052] like Figure 1 As shown, a specific embodiment of the present invention provides a method for a self-sustaining hygroscopic generator based on waste incineration fly ash and waste salt, comprising the following steps:

[0053] (1) washing the waste incineration fly ash with water, adjusting the pH value of the fly ash washing liquid to 9±0.5 with a hydrochloric acid solution; performing solid-liquid separation to obtain a fly ash washing liquid from which heavy metal ions are removed;

[0054] The washing liquid contains a large amount of sodium chloride, potassium chloride and calcium chloride. After washing, a large amount of calcium hydroxide, calcium carbonate, calcium sulfate, silicon dioxide, aluminum oxide and other substances remain in the fly ash, and almost all heavy metals are retained in the solid phase without leaching and migrating into the liquid phase.

[0055] As an example, when washing the fly ash with water, the liquid-to-solid ratio is set to (3-5):1 (L / kg); stirring is maintained for 90 minutes during the washing process, and the rotation speed is 1200 rpm; the concentration of the hydrochloric acid solution used to adjust the pH value is 1M, and the volume is 10%-15% of the volume of the fly ash washing liquid; filter pressing or centrifugation is used for solid-liquid separation.

[0056] (2) Use ICP (Inductively Coupled Plasm) and conductivity meter to test the Na + , K + , Ca 2+ Ion concentration and salinity, calculate the mass percentage of each chloride salt based on ICP results and conductivity data;

[0057] As an example, the ion concentration of sodium, potassium and calcium in the fly ash washing liquid after pickling is directly used, which is about 1:1:3.

[0058] (3) The conductivity meter is calculated as a function operation. The Na in the calculation function is set according to the ICP result. + , K + , Ca 2+ The ion concentration ratio is then calculated weighted by the conductivity values ​​of the individual ions.

[0059] For example, the ICP results show that the ion concentration is more than Na + :K + :Ca 2+ =a:b:c; the conductivity of the solution with a mass fraction of 10wt% of NaCl, KCl, and CaCl2 are A, B, and C respectively; the conductivity of the mixed solution is θ, and the total mass of the solution is m (indirect variable). Then the mass fraction of each component is calculated as: The salinity of the solution is

[0060]

[0061] (4) Weigh 1 g of carbon material and 2 g of surfactant and blend them; the carbon material here is conductive carbon black, and the surfactant is dodecyltrimethylammonium bromide; add 200 ml of deionized water to the mixed powder, put it in an ultrasonic cleaner, and perform ultrasonic treatment for 60 minutes.

[0062] (5) Cut the non-woven fabric into strips with a width of 1 cm, apply the conductive carbon black dispersion obtained in step (4) on the strips, and ensure that more than half of the area of ​​the non-woven fabric strips evenly absorbs the conductive carbon black dispersion each time, then put the strips into a 65°C oven for drying, wait for the non-woven fabric strips to be dried, take them out, and repeat step (5) 8 to 10 times. Use a multimeter to measure the resistance to ensure that the resistance is within the usable range.

[0063] As an example, the non-woven fabric strip used this time is 20 cm long, and the carbon black loading part is (10-12) cm long. The carbon fabric requires a resistance of (5-20) kΩ.

[0064] (6) Take out the non-woven fabric strip fully loaded with conductive carbon black, use a dropper to absorb an appropriate amount of the fly ash water washing liquid in step (4), and drop it on one end of the non-woven fabric strip loaded with conductive carbon black (hereinafter referred to as carbon cloth). After the carbon cloth is completely absorbed, put it in an oven at 85°C for drying. After the carbon cloth is dried, take it out and repeat step (6) 4 to 6 times.

[0065] As an example, in this case, 0.1 ml of fly ash washing liquid was sucked with a dropper each time. The salinity of the fly ash washing liquid was about (10-20) wt%, and the mass of salt added at a single time was (0.01-0.02) g.

[0066] (7) Take out the waste salt moisture-driven carbon cloth that has been impregnated with salt, seal its long edges with insulating tape, and leave space on the short edges for wire connection, so as to obtain a single moisture generator working unit.

[0067] Example 1

[0068] In this embodiment, the waste incineration fly ash is obtained from a waste incineration plant in Zhejiang Province.

[0069] The processing process in this embodiment specifically includes the following steps:

[0070] (1) Wash the waste incineration fly ash with water, and set the washing liquid-solid ratio to 3:1 (L / kg). Add an appropriate amount of 1M industrial hydrochloric acid (about 15% of the total volume of the fly ash washing mixture) during the washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2). The solid part is collected and placed in an oven for drying at room temperature and pressure.

[0071] (2) Use ICP and conductivity meter to test the Na content of the water wash solution + , K + , Ca 2+ Ion concentration and salinity, calculate the mass percentage of each chloride salt based on ICP results and conductivity data;

[0072] After calculation, the mass ratio of NaCl, KCl and CaCl2 in the fly ash washing liquid used this time is 1:1:3.

[0073] (3) The conductivity meter calculates the function and records the concentration based on the ICP result. + , K + , Ca 2+ The ion concentration ratio is then calculated weighted by the conductivity values ​​of the individual ions.

[0074] After calculation, the ICP results show that the ion concentration mass ratio is Na + :K + :Ca 2+ =2:2.9:6; the conductivity of the solution with a mass fraction of 10wt% of NaCl, KCl, and CaCl2 is 110, 78, and 104 respectively; the conductivity of the mixed solution is 192, and the total mass of the solution is m (indirect variable). Then the mass fractions of each component are calculated to be: 3.6%, 3.9%, and 11.7%. The salinity of the solution is about 19.2wt%.

[0075] (4) The carbon material and the surfactant are mixed in a mass ratio of 1:2; the carbon material here is conductive carbon black, and the surfactant is dodecyltrimethylammonium bromide; deionized water is added to the mixed powder so that the concentration of the conductive carbon black is 5 g / L, and the mixture is placed in an ultrasonic cleaner and ultrasonically treated for 60 minutes.

[0076] (5) Cut the non-woven fabric into strips with a width of 1 cm, apply the conductive carbon black dispersion obtained in step (4) on the strips, and ensure that more than half of the area of ​​the non-woven fabric strips evenly absorbs the conductive carbon black dispersion each time, then put the strips into a 65°C oven for drying, wait for the non-woven fabric strips to be dried, take them out, and repeat step (5) 10 times. Use a multimeter to measure the resistance to ensure that the resistance is within the usable range.

[0077] After testing, the non-woven fabric strip used this time is 20cm long, and the carbon black loading part is 10cm long. The resistance of the carbon fabric is 5.67kΩ.

[0078] (6) Take out the non-woven fabric strip fully loaded with conductive carbon black, use a dropper to absorb 0.1 ml of the fly ash water washing liquid in step (4), and drop it on one end of the non-woven fabric strip loaded with conductive carbon black (hereinafter referred to as carbon cloth). After the carbon cloth is completely absorbed, put it in an oven at 85°C for drying, and wait until the carbon cloth is completely dried before taking it out. Repeat step (6) 4 times.

[0079] (7) Take out the waste salt moisture-driven carbon cloth that has been impregnated with salt, seal its long edge with insulating tape, and leave the short edge for wire connection. In this way, a single SMIEG working unit is obtained. After testing, its open circuit potential is 0.84V, short circuit current is 14μA, and output power is 11.8μW.

[0080] Example 2

[0081] In this embodiment, the waste incineration fly ash is selected the same as that in Embodiment 1.

[0082] The operation process of this embodiment is consistent with that of embodiment 1, and some parameters in each step are adjusted as follows:

[0083] (1) Take out the waste incineration fly ash after low-temperature thermal decomposition from the tubular furnace, wash the waste incineration fly ash with water, set the water washing liquid-solid ratio to 4:1 (L / kg), add an appropriate amount of 1M industrial hydrochloric acid (about 11% of the total volume of the fly ash water washing mixture) during the water washing process, stir with magnetic force for 90 minutes at a speed of 1200 rpm; monitor the pH value of the mixture in real time and control the pH at 9±0.5. Vacuum filter the washed mixture for solid-liquid separation to obtain acidified and adjusted washed fly ash, and separate the solid-liquid mixture after acid leaching. The liquid part is the acid leaching liquid and enters step (2), and the solid part is collected and placed in an oven for drying at room temperature and pressure.

[0084] (2) Use ICP and conductivity meter to test the Na content of the water wash solution + , K + , Ca 2+ Ion concentration and salinity, calculate the mass percentage of each chloride salt based on ICP results and conductivity data;

[0085] After calculation, the mass ratio of NaCl, KCl and CaCl2 in the fly ash washing liquid used this time is 1:1:3.2.

[0086] (3) The conductivity meter calculates the function and records the concentration based on the ICP result. + , K + , Ca 2+ The ion concentration ratio is then calculated weighted by the conductivity values ​​of the individual ions.

[0087] After calculation, the ICP results show that the ion concentration mass ratio is Na + :K + :Ca 2+ =2.2:3.1:6.4; the conductivity of the solution with a mass fraction of 10wt% of NaCl, KCl, and CaCl2 is 110, 78, and 104 respectively; the conductivity of the mixed solution is 146, and the total mass of the solution is m (indirect variable). Then the mass fractions of each component are calculated to be: 2.8%, 3.0%, and 8.9%. The salinity of the solution is about 14.6wt%.

[0088] (4) The carbon material and the surfactant are mixed in a mass ratio of 1:2; the carbon material here is conductive carbon black, and the surfactant is dodecyltrimethylammonium bromide; deionized water is added to the mixed powder so that the concentration of the conductive carbon black is 8 g / L, and the mixture is placed in an ultrasonic cleaner and subjected to ultrasonic treatment for 60 minutes.

[0089] (5) Cut the non-woven fabric into strips with a width of 1 cm, apply the conductive carbon black dispersion obtained in step (4) on the strips, and ensure that more than half of the area of ​​the non-woven fabric strips evenly absorbs the conductive carbon black dispersion each time, then put the strips into a 65°C oven for drying, wait for the non-woven fabric strips to be dried, take them out, and repeat step (5) 9 times. Use a multimeter to measure the resistance to ensure that the resistance is within the usable range.

[0090] After testing, the non-woven fabric strip used this time is 20cm long, and the carbon black loading part is 12cm long. The resistance of the carbon fabric is 10.49kΩ.

[0091] (6) Take out the non-woven fabric strip fully loaded with conductive carbon black, use a dropper to absorb 0.1 ml of the fly ash water washing liquid in step (3), and drop it on one end of the non-woven fabric strip loaded with conductive carbon black (hereinafter referred to as carbon cloth). After the carbon cloth is completely absorbed, put it in an oven at 85°C for drying, and wait until the carbon cloth is completely dried before taking it out. Repeat step (6) 5 times.

[0092] (7) Take out the waste salt moisture-driven carbon cloth that has been impregnated with salt, seal its long edge with insulating tape, and leave the short edge for wire connection. In this way, a single SMIEG working unit is obtained. After testing, its open circuit potential is 0.79V, short circuit current is 13μA, and output power is 9.48μW.

[0093] As shown in Table 1, the treated fly ash water wash provided in Example 1 is pure high-chloride salt wastewater, in which the main anions and cations are Na + , K + , Ca 2+ , Cl — .

[0094]

[0095] like Figure 2 As shown, the wet gas generator based on the utilization of waste incineration fly ash and waste salt prepared in Example 1, when the hygroscopic layer prepared with hygroscopic waste salt is exposed to the environment, the hygroscopic part will spontaneously absorb moisture from the ambient air, forming a water content gradient in the wet gas generator device. The absorbed water will flow from the hygroscopic part to the evaporation part with low water content through the nanochannel. Because the partial pressure of water in the air is always lower than the saturated vapor pressure, under ambient conditions, the water stored in the evaporation part will evaporate spontaneously. Finally, the vapor pressure difference between the hygroscopic part and the area near the evaporation part drives the water molecules to complete convection, establishing a long-lasting artificial water cycle for continuous power generation.

[0096] like Figure 3 As shown, in Figure 3 In (a), when the ambient humidity (RH) is 20%≤RH≤80%, as the ambient humidity increases, the short-circuit current of the wet gas generator unit prepared in Example 1 will also increase; Figure 3 In (b), when the ambient humidity (RH) is 20%≤RH≤80%, as the ambient humidity increases, the open circuit voltage development rate and the steady-state potential of the wet gas generator unit also increase accordingly.

[0097] like Figure 4 As shown, in an environment of RH=80%, the wet gas generator prepared in Example 1 can maintain long-term stable operation for more than 1000 min, with an open circuit voltage of 0.80 V and a short circuit current of 14 μA.

[0098] like Figure 5 As shown, Figure 5 (a) is the short-circuit current characteristic of a parallel circuit composed of 1 to 4 wet gas generator units prepared in Example 1; Figure 5(b) is the open circuit voltage characteristic of a series circuit composed of 1 to 4 wet gas generator units prepared in Example 1. In both parallel and series models, the wet gas generator units maintain good superposition linearity and show marginal effects. This experiment proves that it is feasible to improve the output performance of wet gas generator units by increasing the number of units in series or in parallel.

[0099] In summary, the method of a self-sustaining hygroscopic generator based on the utilization of waste incineration fly ash and waste salt provided by the present invention has clean, low-carbon, long-term sustainable power conversion. The emerging moisture-driven energy (wet gas power generation) is a promising green energy source that can be used as the next generation power source for a wide range of Internet of Things and wearable applications. It has the characteristics of inexhaustible, sustainable and highly convenient. The development of green wet gas generators is also important for finding completely clean, low-carbon and sustainable energy alternatives. It requires not only continuous energy and conversion processes, but also the use of environmentally friendly materials and manufacturing processes. However, previous work has mainly focused on power output performance, and the materials used, such as electrospun nanofibers and partially reduced graphene oxides, usually involve complex, power-consuming and expensive manufacturing processes. Therefore, it is meaningful to explore green materials with convenient manufacturing methods. The carbon black skeleton and hygroscopic waste salt used in the present invention bid farewell to the high manufacturing cost and preparation threshold of traditional hygroscopic generators, which further improves its engineering and commercial promotion potential. Therefore, the invention is a functional utilization technology of waste incineration fly ash with great engineering practical application prospects, low cost, low carbon and environmental protection.

[0100] (1) This method uses low-cost and easily available conductive carbon black as the conductive skeleton of the wet gas generator and widely used non-woven fabrics as the water transmission channel of the wet gas generator. Compared with graphene-based materials and other gel materials, it does not require complicated preparation or processing steps, is easy to obtain, has a variety of alternative options, and is more suitable for industrialization and commercialization.

[0101] (2) The present invention uses hygroscopic chloride salts as the spontaneous hygroscopic layer. Compared with other hygroscopic materials and lithium chloride which is also a hygroscopic chloride salt, the industrial acquisition of sodium potassium calcium chloride salts is simpler, the source is more extensive, and the cost is lower.

[0102] (3) The hygroscopic chloride salt used in the present invention is derived from the extraction and recovery of chloride salts in fly ash from the incineration of hazardous waste, which is a technology for converting hazardous waste into functional advanced energy materials.

[0103] (4) The wet gas generator prepared by the present invention can work in an environment with RH ≥ 30%, has good environmental adaptability, and has a wide range of applications.

[0104] Obviously, those skilled in the art may make various subsequent applications, supplements, modifications and variations to the present invention without departing from the spirit and scope of the present invention. If various applications, supplements, modifications and variations based on the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include such applications, supplements, modifications and variations.

Claims

1. A method for preparing a wet gas generator based on fly ash and waste salt from garbage incineration, characterized in that: include: (1) washing waste incineration fly ash to obtain a fly ash aqueous solution, adjusting the pH value of the fly ash aqueous solution to 8.5-9.5, and obtaining a fly ash aqueous solution from which heavy metal ions are removed after solid-liquid separation; The carbon material and the surfactant are mixed to obtain a mixed powder, the mixed powder is added to deionized water, and ultrasonic treatment is performed to obtain a conductive dispersion, and the conductive dispersion is coated and dried on the surface of the non-woven fabric for multiple times until a preset resistance value is reached to obtain a carbon cloth; (2) adding a fly ash aqueous solution from which heavy metal ions have been removed to one end of the carbon cloth until the carbon cloth has completely absorbed the ions and then drying the solution, and repeating step (2) multiple times to obtain a waste salt moisture driven carbon cloth; (3) Connect the waste salt moisture-driven carbon cloth to the wire to obtain a moisture generator.

2. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: The stirring time of the water washing is 1 to 1.5 hours, the rotation speed is 800 to 1200 r / min, and the liquid-to-solid ratio of the aqueous solution to the waste incineration fly ash is (3 to 5):1 (L / kg).

3. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: The salinity of the fly ash aqueous solution from which heavy metal ions have been removed is 10 wt % to 20 wt %.

4. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: Before the fly ash aqueous solution from which heavy metal ions are removed is added dropwise to one end of the carbon cloth, the mass concentrations of Na, K, and Ca ions and the corresponding masses of chloride salts in the fly ash aqueous solution from which heavy metal ions are removed are measured, and based on pre-set chloride salt mass standards for Na, K, and Ca ions, additional chloride salts that do not meet the standards are added.

5. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 4, characterized in that: The Ca ion concentration in the fly ash aqueous solution from which heavy metal ions are removed is 60% to 70%.

6. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 4, characterized in that: The chloride salt includes NaCl, KCl or CaCl2, with a mass fraction of more than 99%.

7. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: The carbon material is conductive carbon black, and the surfactant is dodecyltrimethylammonium bromide.

8. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: In the conductive dispersion, the content of the carbon material is 5-10 g / L, and the ultrasonic time is 1-2 h.

9. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: The chloride content loaded on the waste salt moisture driven carbon cloth is (0.04-0.08) g / cm 2 .

10. The method for preparing a wet gas generator based on waste incineration fly ash and waste salt according to claim 1, characterized in that: Step (3) comprises the following steps: One side of the waste salt moisture-driven carbon cloth is connected to a wire, and the side not connected to the wire is insulated and packaged to obtain a moisture generator unit.